Case series on uterine rupture depicting the atypical presentations in the labour room - Aggarwal, Srishti; Jindal, Monika; Minhas, Santosh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Uterine rupture is the complete division of all the three layers of uterus. Most uterine ruptures occur during labor in pregnant women, most commonly seen in previously scarred myometrium. Consequences of uterine rupture depend on the time between diagnosis of uterine rupture and intervention, and can be as grave as fetal and maternal death. Vigilance and avid action by the obstetrician can lead to better outcomes. Case 1 represented a 28-year-old moderately anemic G4P2L2A1 having previous 2 LSCS at POG 39 weeks 1 day presented in COVID emergency in active labour and was found to have a uterine scar rupture (5 cm rent) extending towards bladder wall with shoulder presenting on rent. A live female baby with thick meconium staining was delivered and uterine repair along with bilateral tubectomy was performed. Case 2 represented a 21-year-old primigravida with breech presentation at a gestation of 34 weeks 6 days with preterm labour pains who had been referred to our centre. Decision for LSCS was taken and on entering the abdomen rupture uterus with an inverted T-shaped rent in the upper segment extending up to the fundus was seen. A stillborn male fetus was delivered through the rent, followed by successful uterine repair. In spite of massive blood loss, the mother had survived. Case 3 represented a 30-year-old grand multipara at a gestation of 38 weeks 3 days with ultrasound documented fetal demise with fetal hydrocephalus and holoprosencephaly with labour pains was taken up for laparotomy due to suspicion of uterine rupture based on examination findings. Intra-operatively, baby was found lying in the peritoneal cavity with an unsalvageable uterus with a rupture in lower uterine segment and left lateral wall extending upto round ligament above and cervix below. A stillborn male fetus was delivered and peripartum subtotal hysterectomy with left salpingoophorectomy and right salpingectomy was done with a good maternal outcome. The above series suggest that the signs and symptoms of uterine rupture are usually variable and nonspecific, hence posing a challenge for the diagnosis. Early diagnosis and timely intervention by the obstetrician, can help us to improve the fetal and maternal outcome drastically.